Analysis of Pedestrian Travel Demand for Bus Trans Semarang through 3D Method (Density, Diversity, Design) - Rakhmatulloh, Anita Ratnasari; Dewi, Diah Intan Kusumo; Nugraheni, Dinar Mutiara Kusumo (Universitas Negeri Semarang, 2020)
The growing number of private transportation ownership from year to year creates congestion problems, especially in urban areas. Public transportation conditions such as the Rapid Transit Bus (BRT) are an alternative way to use transportation. BRT Trans Semarang Corridor 1 is the busiest public transportation route in Semarang City that stretches from Mangkang Terminal to Penggaron Terminal. About 50% of the passengers of BRT Trans Semarang Corridor 1 chose to walk to and from the bus stops. However, in reality, currently, the conditions of the pedestrian paths are less than optimal in creating pedestrian comfort, and the integration system is still minimal with various modes. The purpose of this study is to identify a travel demand model suitable for pedestrian BRT Trans Semarang Corridor 1 passenger using the new urbanism 3D approach (Density, Diversity, Design). Where the data collection for analysis needs using naturalistic observation techniques by looking at the condition of the object of research in a more real way directly to the field. Density analysis used descriptive statistical analysis methods and simulated interpolation of population and building density data using the ArcGIS 10.3 application to generate pedestrian demand for their environmental density. In analyzing diversity using the land-use distribution simulation method with ArcGIS 10.3 and FAR (Floor Area Ratio) analysis using the 2016 Sketchup simulation. Compile a pedestrian path model recommendation under pedestrian demand.